Groundwater Artificial Recharge Solutions for Integrated Management of Watersheds and Aquifer Systems under Extreme Drought Scenarios - Lobo Ferreira, J. P. C. (2011)
This paper addresses groundwater artificial recharge solutions for integrated management of watersheds and aquifer systems under extreme drought scenarios. Based on a lecture presented by Dr. JP Lobo Ferreira at UNESCO’s International Year of Planet Earth (IYPE) Workshop held in Oslo, Norway, August 2009, the conceptual idea of Aquifer Storage and Recovery (ASR) is considered, in this paper, as one of the scientific based solutions towards scientific based mitigation measures to climate variability and change in many parts of the world. In Portugal two European Union sponsored 6th Framework Programme for Research Projects have been addressing this topic, namely GABARDINE Project on “Groundwater artificial recharge based on alternative sources of water: Advanced integrated technologies and management” (cf. http://www.lnec.pt/organizacao/dha/organization/dha/nas/estudos_id/gabardine) and the Coordinated Action ASEMWATERNet, a “Multi-Stakeholder Platform for ASEM S&T Cooperation on Sustainable Water Use” (cf. http://www.lnec.pt/organizacao/dha/nas/estudos_id/asemwaternet and http://www.asemwaternet.org.pt). This paper addresses selected achievements of those Projects.